2018
DOI: 10.3177/jnsv.64.185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of French Pine Bark Extract Chewing Gum on Oral Malodor and Salivary Bacteria

Abstract: Summary Frequent or persistent malodor (halitosis) represents a considerable embarrassment to those affected. French pine bark extract, Pycnogenol ® (PYC), has displayed antibacterial activity against a broad range of bacterial species. In the present study, anticipated benefits of PYC on diminishing halitosis were investigated. Ten healthy males and 11 females, aged 40.1612.3 y, were recruited based on threshold breath sulfur compounds presence, diagnosed by portable gas chromatography. Subjects were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…A Tabela 2 descreve os 17 artigos incluídos, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] sendo estes a maioria ensaios clínicos randomizados, publicados em 2016 (47,05%). Com relação a análise qualitativa dos artigos selecionados, 6 pesquisas possuem baixa qualidade metodológica e 11 artigos são metodologicamente aceitáveis e passíveis de reprodução e aplicação (Tabela 3).…”
Section: Resultsunclassified
“…A Tabela 2 descreve os 17 artigos incluídos, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] sendo estes a maioria ensaios clínicos randomizados, publicados em 2016 (47,05%). Com relação a análise qualitativa dos artigos selecionados, 6 pesquisas possuem baixa qualidade metodológica e 11 artigos são metodologicamente aceitáveis e passíveis de reprodução e aplicação (Tabela 3).…”
Section: Resultsunclassified
“…The herbal mucoadhesive tablet examined by Sterer and co-workers (2013) reduced VSC's and the organoleptic score significantly better than placebo. Other studies investigating herbal products showed less remarkable results (Rosing et al, 2002, Sakagami et al, 2016, Farina et al, 2012, Watanabe et al, 2018.…”
Section: Herbal Substancesmentioning
confidence: 95%
“…For the VSCs measurement, patients were asked to breath in a sterile syringe that was immediately injected into the OralChroma and measurements were taken according to the manufacturer's instructions. Based on the measurements of the two main intraoral halitosis gases, H2S and MM, individuals were classified into four groups (Figure 1): a control group (Ctr) of halitosis-free individuals with both gasses below the halitosis-threshold (<112 ppb for H2S and <26 ppb for CH3SH, [13][14][15]) and three halitosis groups, namely the MM group (<112 ppb H2S and >26 ppb CH3SH), the H2S group (>112 ppb H2S and <26 ppb CH3SH), and the MM-HS group (>112 ppb H2S and >26 ppb CH3SH). In each group, the 10 individuals that best fulfilled the criteria (i.e., lowest or highest ppb of one or both of the gasses) were selected for RNAseq analysis.…”
Section: Vscs Measurements and Patient Classificationmentioning
confidence: 99%
“…The last two have been unequivocally related to intra-oral halitosis and appear to be responsible for up to 90% of oral VSCs [11] whereas dimethyl sulfide is considered to be implicated mainly in extra-oral blood borne halitosis [12]. Current clinical literature establishes specific threshold values for halitosis diagnosis for H2S (112 ppb), CH3SH (26 ppb) and [CH3]2S (8 ppb) [13][14][15]. Previous epidemiological reports suggest that other odoriferous molecules could also be responsible or contribute to bad breath, including volatile aromatic compounds and (poly)amines, short/medium-chain fatty acids or organic acids, alcohols, volatile aliphatic compounds, aldehydes and ketones [16].…”
Section: Introductionmentioning
confidence: 99%